Ferritin-like family proteins in the anaerobe Bacteroides fragilis: when an oxygen storm is coming, take your iron to the shelter - Rocha, Edson R. (2013)
Bacteroides are gram-negative anaerobes and one of the most abundant members the lower GI tract microflora where they play an important role in normal intestinal physiology. Disruption of this commensal relationship has a great impact on human health and disease. Bacteroides spp. are significant opportunistic pathogens causing infections when the mucosal barrier integrity is disrupted following predisposing conditions such as GI surgery, perforated or gangrenous appendicitis, perforated ulcer, diverticulitis, trauma and inflammatory bowel diseases. B. fragilis accounts for 60–90 % of all anaerobic infections despite being a minor component of the genus (<1 % of the flora). Clinical strains of B. fragilis are among the most aerotolerant anaerobes. When shifted from anaerobic to aerobic conditions B. fragilis responds to oxidative stress by inducing the expression of an extensive set of genes involved in protection against oxygen derived radicals and iron homeostasis. In Bacteroides, little is known about the metal/oxidative stress interactions and the mobilization of intra-cellular non-heme iron during the oxidative stress response has been largely overlooked. Here we present an overview of the work carried out to demonstrate that both oxygen-detoxifying enzymes and iron-storage proteins are essential for B. fragilis to survive an adverse oxygen-rich environment. Some species of Bacteroides have acquired multiple homologues of the iron storage and detoxifying ferritin-like proteins but some species contain none. The proteins found in Bacteroides are classical mammalian H-type non-heme ferritin (FtnA), non-specific DNA binding and starvation protein (Dps) and the newly characterized bacterial Dps-Like miniferritin protein. The full contribution of ferritin-like proteins to pathophysiology of commensal and opportunistic pathogen Bacteroides spp. still remains to be elucidated.